Mandelstam – Planck Polemics and its Representation in the Soviet Scientific Literature: Ideological Metamorphoses - Pechenkin, Alexander (Problemos, 2021)
The L. I. Mandelstam - M. Planck polemics concerning the theory of dispersion (1907-1908) are taken under consideration. Mandelstam attacked Planck’s theory published in 1904. Planck reacted by publishing a short reply in 1907. Mandelstam was not satisfied and published a paper where he provided a more detailed calculation (1908). Planck criticized his approach again (1908). Mandelstam published two more papers, but Planck did not react to these publications.From a historical point of view it is interesting that in the Soviet scientific literature, Mandelstam’s position was almost unanimously considered to be correct and powerful. The situation changed after the collapse of the Soviet Union. Russian physicists came to treat Planck’s position as the correct one. In this connection, the problem of scientific objectivity arises. The author emphasizes the ideological context of the scientific interpretation of facts. The phenomena of progressivism and introjection are taken under consideration.
Keywords: optics; dispersion; polemics; State ideology; the ideological engine